DESIGN COMPUTERIZED PERSONNEL INFORMATION SYSTEM PT OMU - Indra Toni; Oon Amroni, Ir., MSc Oon Amroni, Ir., MSc (Jurnal Sistem Informasi, 1991)
In this research aims to change the personnel staffing data processing, which is stillperformed in the conventional / manual, with the help of computer hardware for fastdata processing, the company makes computerized data processing personnel in orderto accelerate the process of doing data processing personnel and presenting reports -reports / information to the right, quickly and accurately.